Pengaruh Kemampuan Manajerial dan Lingkungan Industri terhadap Kemampuan Organisasi, Strategi Bersaing, dan Kinerja Perusahaan (Studi pada Industri Kecil Meubel Kayu di Sulawesi Tenggara) - Hajar, Ibnu (Universitas Brawijaya, Indonesia, 2012)
Abstract: The objective of research is to measure and to analyze the effect of managerial ability and industrial environment on organizational capability, competitive strategy and company performance. Research is conducted at wood furniture small industry at Southeast Sulawesi with the sample of 143 managers/owners of company as the respondent. Research analysis tool is Partial Least Square (PLS). Result of research indicates that the managerial ability has positive and significant effect on organizational capability,competitive strategy, and company performance. Industrial environment has negative and significant effect on organizational capability and company performance. Industrial environment has negative and nonsignificant effect on competitive strategy. The organizational capability has positive and significant effect on competitive strategy and company performance. The competitive strategy has positive effect on company performance.